Perbandingan Tingkat Stres Berorganisasi Internal Remaja Berdasarkan Tipe Kepribadian Di PPM MBS Putri Yogyakarta - Wisda Via Nurfallah; Novia Fetri Aliza (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to compare the level of stress in an organization among high school adolescents based on the personality types of Introvert and Extrovert at PPM Muhammadiyah Boarding School Putri Sleman Yogyakarta. Adolescents who are involved in organizations get more stressors than adolescents who are not involved in organizations. Stress itself is a condition of a person where there is a mismatch between the demands obtained and the abilities possessed. One of the factors that can affect stress is personality. This study used the purposive sampling technique as many as 140 respondents who met the research criteria. The research design used was quantitative using a comparative descriptive method. The data were collected using a personality type questionnaire and a stress level questionnaire. The hypothesis testing data used the Independent Sample T-Test. The results of the Independent Sample T-Test study obtain the value of Sig. (2- talied) of 0.001, which means the value of Sig. (2-tailed) is less than (<) 0.05. The conclusion in this study is that there are differences in the level of stress in an organization among high school adolescents based on the personality types of Introvert and Extrovert at PPM Muhammadiyah Boarding School Putri Sleman Yogyakarta. Adolescents with extroverted personality types are more susceptible to stress than adolescents with introverted personality types.